Pengaruh Terapi Brain Gym TerhadapPeningkatan Fungsi Kognitif Pada Lanjut UsiaDi Posyandu Lanjut Usia Desa PucanganKartasura - Hanafi, Abdullah; , Agus Sudaryanto, S.Kep., Ns., M.Kes (2014)
The increasing age of humans, the aging process occurs which affects generative changes in humans, one of which is throwback of cognitive function status. Brain Gym is one method of motion and train the brain, which is useful to improve cognitive function, especially in the elderly. The purpose of this study was to determine the effect of Brain Gym on the level of cognitive function in posyandu lansia of Pucangan village Kartasura. This type of research is Quasi Experimental Design with Pretest-Posttest Control Group Design, The population are 286 people. The sampling method used was purposive sampling. Overall sample in this study met the inclusion criteria of 20 people. To compare the cognitive level of the respondents before and after brain exercises using the Mini Mental State Examination (MMSE) were analyzed by paired t-test. Based on the results of the study, respondents had significant cognitive improvement. Analysis of research data in the experimental group using Paired Sample t-test with a significance value (α = 0.05). With tcount -4.452; p = 0.002 <0.05) and the average value sattus cognitive function before the Brain Gym therapy at 19.00 and at 21.80 after intervention. The average level of cognitive elderly control group with tvalue -2.714; (p = 0.024 <0.05). Thus the conclusion can be made that there is an influence of Brain Gym to increase cognitive function in the elderly.